OPTIMIZATION OF KRPL TANI WOMEN'S GROUP AS AN ALTERNATIVE SOURCE OF FAMILY INCOME IN COVID-19 PANDEMIC - Muhammad Syahril; Yenni Marnita (Global Science Society, 2021)
In the midst of the Covid-19 virus attack, agriculture must be a source of strength and savior for the nation. The use of yard land or the so-called Sustainable Food Home Area /”Kawasan Rumah Pangan Lestari (KRPL) in providing food and micro-nutrition needs for the family is important, it needs to be managed properly and preserved so that it can increase family economic income. KRPL is very strategic not only to meet the food and nutritional needs of the family, but also to increase household income especially in the midst of the COVID-19 pandemic as has happened in the last few months. The community service was carried out together with the Ceumpaka Keumang Gampong Alue Pineung Women Farmers Group (KWT), Langsa Timur District, Langsa City, which is one of the areas affected by the COVID-19 outbreak. The entire Community Service Program which is planned to be implemented with a pattern of education and training as well as assistance which includes: 1) implementing nursery development activities to accelerate strengthening of food reserves in the village, 2) developing group demonstration plots, 3) developing new member yards 4) coordinating with the Langsa City Agricultural Service, the East Langsa District Agricultural Extension Center and the Village Head in order to continue and develop post-community service activities. The results of this dedication provide increased knowledge of partners, have a nursery with the concept of plant diversification, have a wider group demonstration plot, increase the use of yards for new members and increase food availability during the Covid-19 pandemic and of course increase the income of group members.